AN EFFECTIVENESS OF HANDLING OF PATIENT COMPLAINTS OF BPJS HEALTH SERVICES AT ROYAL PRIMA HOSPITAL MEDAN - Mei Riauly Wira Purba; Chrismis Novalinda Ginting; Johannes Bastira Ginting (Sean Institute, 2023)
Analyzing data on negative patient complaints can strengthen the ability of health organizations to detect systematic problems in their services, handle complaints properly as a strategy to improve services and maintain long-term relationships with patients. The purpose of this research isto knowthe effectiveness of handling complaints of inpatients BPJS health services at General Hospital Royal Prima Medan. This type of research ismix methodnamely a combination of quantitative and qualitative research. The population and this study are patientsBPJSwho came for treatment at the Inpatient Installation of General Hospital Royal Prima Medan in the last 3 months totaling 1,653 patients, with a quantitative research sample of 200 patients and 7 qualitative informants. For quantitative data analysis using univariate analysis and for qualitative usedata analysis model Miles and Hubermand consists of data reduction data, data presentation, drawing conclusions. Data in this study were collected using questionnaires and interviews. For supporting factors such as the availability of complete facilities and infrastructure for patients to submit complaints, there is also a budget for handling patient complaints and at General Hospital Royal Prima Medan the handling of patient complaints is handled in accordance with existing SOPs. The conclusion of this study is that the handling of complaints of inpatient BPJS by General Hospital Royal Prima Medan has been running effectively